Legal Challenges to Generative AI, Part I: Questioning the legality of using in-copyright works for training data and producing outputs derived from copyrighted training data. - Samuelson, Pamela (Communications of the ACM, 2023)
The article focuses on the legal challenges surrounding generative artificial intelligence (AI) and its implications for copyright laws. It reports specifically on the Doe vs. GitHub lawsuit in which a class of programmers claim their legal rights were violated when GitHub's Copilot and OpenAI's Codex AI programs used publicly available open source code that the litigants developed as training data for the programs.